2023
DOI: 10.1038/s41598-023-30424-2
|View full text |Cite
|
Sign up to set email alerts
|

Additional flight delays and magnetospheric–ionospheric disturbances during solar storms

Abstract: Although the sun is really far away from us, some solar activities could still influence the performance and reliability of space-borne and ground-based technological systems on Earth. Those time-varying conditions in space caused by the sun are also called solar storm or space weather. It is known that aviation activities can be affected during solar storms, but the exact effects of space weather on aviation are still unclear. Especially how the flight delays, the top topic concerned by most people, will be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The average delay time during solar X-ray events is 44.75 min (median: 25 min), which is 7.67 min (median: 5 min) longer than during quiet periods. These findings demonstrate that flight departure delays will increase during solar X-ray events, consistent with our previous study on arrival delays 21 . The longitudinal effect (local time) is a key factor that affects the Earth's response to solar flares 33 .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The average delay time during solar X-ray events is 44.75 min (median: 25 min), which is 7.67 min (median: 5 min) longer than during quiet periods. These findings demonstrate that flight departure delays will increase during solar X-ray events, consistent with our previous study on arrival delays 21 . The longitudinal effect (local time) is a key factor that affects the Earth's response to solar flares 33 .…”
Section: Resultssupporting
confidence: 92%
“…It has been previously demonstrated that there exists a linear correlation between the arrival delay and departure delay 27,28 . In addition, our previous study 21 has examined the effect of space weather on arrival delays, which can be contrasted with the present work. Thus, the focus of the current analysis is on the departure delay rather than the arrival delay.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations